2016
DOI: 10.20463/jenb.2016.0055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silk Peptides Administration on Fat Utilization Over a Whole Day in Mice

Abstract: [Purpose]The aim of the present study was to investigate the effects of treatment with silk peptides (SP) on resting energy expenditure over a 24-h period and clarify the molecular mechanism underlying its enhancement of fat utilization in mouse skeletal muscles.[Methods]Sixteen male ICR mice (6-weekold) were divided into two groups and treated with distilled water and SP (CON and SP treatment groups, respectively). SP were dissolved in distilled water and administered to the SP group at 800 mg/kg while the CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The resting metabolic rate (RMR), which serves as an approximation of the metabolic phenotype, was measured at 8 and 16 weeks of age. Measurements were performed for 24 hours as previously described [ 16 ] in a metabolic chamber with an open-circuit system (WSMR-1400, Westron, Japan). In order to reduce stress, the mice were transferred to the chamber two hours before measurement initiation.…”
Section: Methodsmentioning
confidence: 99%
“…The resting metabolic rate (RMR), which serves as an approximation of the metabolic phenotype, was measured at 8 and 16 weeks of age. Measurements were performed for 24 hours as previously described [ 16 ] in a metabolic chamber with an open-circuit system (WSMR-1400, Westron, Japan). In order to reduce stress, the mice were transferred to the chamber two hours before measurement initiation.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary SP is a natural material isolated from Bombyx mori that is known to have effects on metabolism [27,47]. In recent studies, it is reported that hydrolyzed proteins are efficiently absorbed in the small intestine [48].…”
Section: Discussionmentioning
confidence: 99%
“…The mice were placed in exercise metabolism chambers for adaptation 1 h before the experiment. Respiratory gas was measured using an open-circuit apparatus in accordance with the methods proposed in previous studies [ 25 26 ].…”
Section: Methodsmentioning
confidence: 99%